Utilization of montmorillonite as a refining solution for the treatment of ametryn, a second generation of pesticide. Issue 4 (August 2017) - Shattar, S.F.A.; Zakaria, N.A.; Foo, K.Y.
Graphical abstract: Highlights: This study identified the novel application of natural montmorillonite. A refining solution for the treatment of ametryn has been attempted. The adsorption capacity for ametryn was 188.68 mg/g. The adsorption modelling, kinetic, and thermodynamic were outlined. The great feasibility for the remediation of hazardous pesticides was verified Abstract: This study reported the feasibility of natural montmorillonite as a refining solution for the adsorptive treatment of ametryn pesticide. The adsorption performance was evaluate with respect to the initial concentrations, contact time and solution pH. Equilibrium data were simulated using the nonlinear Langmuir, Freundlich and Temkin isotherm models, and kinetic equations. The physical and chemical properties were examined using the Scanning Electron Microscopy (SEM), Fourier-Transform Infrared (FTIR) Spectroscopy, nitrogen adsorption-desorption curve, and zero-point-of-charge. Results showed that the equilibrium data were well fitted to the Langmuir isotherm model and pseudo-second order kinetic equation, with a monolayer adsorption capacity of 188.81 mg/g. The natural montmorillonite illustrated the high Brunaeur–Emmet–Teller (BET) surface area and total pore volume of 164.79 m 2 /g and 0.271 cm 3 /g, respectively, with a pore diameter of 65.74 Å. Thermodynamic study demonstrated that the adsorption process was spontaneous and endothermic in nature. The findings revealed the potential of montmorillonite as an outstanding and viable source of natural adsorbent for the successive uptake of ametryn from the contaminated water streams.